THE HISTORICAL EXPERIENCE OF INTERFAITH RELIGIOUS TOLERANCE IN UZBEKISTAN (Ustozlar uchun, 2025)
This article explores the historical experience of interfaith tolerance in Uzbekistan, tracing its roots from the ancient Silk Road civilization to the modern period of national independence. Drawing upon historical documents, UNESCO reports, and the Constitution of the Republic of Uzbekistan, the study analyzes how coexistence among Muslims, Christians, Jews, Buddhists, and other religious groups has contributed to social harmony and national identity. It also highlights contemporary state policies that promote interreligious dialogue, cultural pluralism, and civil peace. The findings show that interfaith tolerance in Uzbekistan is not a recent political construct but a deeply rooted social tradition formed through centuries of cultural interaction and mutual respect.¹